Eksperimenter med flækkepilespidser – Studier af pilespidser fra grubekeramisk kultur - Bye-Jensen, Peter (Kuml, 2011)
Experiments with arrowheads of flint An investigation of tanged points from the Pitted Ware culture This article presents a thematic use-wear analysis of type A tanged points from the Pitted Ware culture. The Pitted Ware culture was contemporary with the late Middle Neolithic Funnel Beaker culture and the early Single Grave culture. The main focus of this article is on an investigation of type A tanged points through a combination of micro and macro use-wear analysis. Together with cylindrical flake cores, and ornamentation in the form of round pits and horizontal lines on the culture’s pottery, type A tanged points date the oldest phase of the Pitted Ware culture. The sample of tanged points which was analysed comes from Kainsbakke, Kirial Bro, Hesselø and Anholt. My goal has been to investigate the following questions by way of use-wear analysis: Do the selected tanged points show any signs of having been used as projectiles? Was the type A0 arrowhead, without a tang, used as an arrowhead or did it have other functions? Have tanged points in general been used for purposes other than as projectiles? How do the tanged points relate to the question of re-shafting? How do the experimental replica tanged points compare with their archaeological counterparts? The relationship of type A0 tanged points to the subsequent types A1-A3 was questioned by Malmer in an article on the early Pitted Ware culture site of Jonstorp RA. The reason for not including type A0 within type A is its lack of a tang. The basis of any micro-wear analysis is an experimental programme. In my case, this comprised three parts: The manufacture of experimental flint replicas of type A tanged points, shafting these replicas and shooting the replica arrows into an authentic target. The target chosen for my experiments was a Sika deer (Cervus nippon). The Sika deer is anatomically similar to the red deer, one of the best represented wild animals at Kainsbakke. On the basis of my experimental results, I can conclude that the type A0 arrowhead performs well as a projectile. Diagnostic macro- and micro-wear traces were observed on all subtypes of the experimental tanged points. In addition, 11 of the archaeological tanged points examined showed diagnostic macro- and micro-wear identical to that on the experimentally produced examples. This means that the type A0 should be considered an arrowhead within the type A tanged point typology. Additionally, none of the archaeological arrowheads showed any evidence of other use-wear other than that found on projectiles. Traces of shafting could be seen on both experimental and archaeological arrowheads. In this article, I discuss the morphology of type A tanged points versus their effectiveness as projectiles and the general results of my experiments. In conclusion, I suggest that there was an alternative target for tanged points associated with the Pitted Ware culture (types A, B and C). The chronological shift from type A to type C arrowheads could be related to a growing use of arrowheads as weapons against humans. In association with these types of arrowhead, we find examples of violent disputes, for example as seen in the case of the Iceman Ötzi, and others. Peter Bye Silkeborg Museum